2018
DOI: 10.3389/fendo.2018.00267
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Actions of Fibroblast Growth Factor-23

Abstract: Fibroblast growth factor-23 (FGF23) is a bone-derived hormone suppressing phosphate reabsorption and vitamin D hormone synthesis in the kidney. At physiological concentrations of the hormone, the endocrine actions of FGF23 in the kidney are αKlotho-dependent, because high-affinity binding of FGF23 to FGF receptors requires the presence of the co-receptor αKlotho on target cells. It is well established that excessive concentrations of intact FGF23 in the blood lead to phosphate wasting in patients with normal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 71 publications
1
81
0
Order By: Relevance
“…Thereby, high dietary phosphorus is associated with increased risk for bone fractures, as shown in a study of 2420 Brazilian individuals in whom every 100 mg of dietary phosphorus intake increased the risk of fracture by 9% [ 241 ]. Recent insights suggest that FGF23 (whose levels are determined by P i concentrations) may impair bone matrix mineralization independently of calcium by transcriptionally suppressing TNAP (although this effect also suppresses OPN) [ 242 , 243 ]. High phosphate containing soft drinks may finally affect dental mineralization, as discussed later in this review.…”
Section: Importance Of Dietary Phosphorus For Bone Healthmentioning
confidence: 99%
“…Thereby, high dietary phosphorus is associated with increased risk for bone fractures, as shown in a study of 2420 Brazilian individuals in whom every 100 mg of dietary phosphorus intake increased the risk of fracture by 9% [ 241 ]. Recent insights suggest that FGF23 (whose levels are determined by P i concentrations) may impair bone matrix mineralization independently of calcium by transcriptionally suppressing TNAP (although this effect also suppresses OPN) [ 242 , 243 ]. High phosphate containing soft drinks may finally affect dental mineralization, as discussed later in this review.…”
Section: Importance Of Dietary Phosphorus For Bone Healthmentioning
confidence: 99%
“…Furthermore, FGF23 reduces renal production of 1,25(OH)2D3 [85] and PTH secretion [96]. FGF23 suppresses the expression of 1α-hydroxylase enzyme in the kidney and induces the synthesis of 25-hydroxyvitamin D24-hydroxylase enzyme; this mechanism leads to a reduced conversion of 25(OH)D into 1,25(OH)2D and increased catabolism of 25(OH)D and 1,25(OH)2D3 into inactive carboxylic acids [97,98] (Figure 2). The Paracalcitol and ENdothelial fuNction in chronic kidneY disease (PENNY) study [99] showed that paricalcitol reduced serum PTH (−75.1 pg/mL, 95% CI −90.4 to −59.8; p < 0.001) and its action is linked to increased FGF23 levels ( + 107 pg/mL, 95% CI 44 to 170; p = 0.001).…”
Section: Fgf23-klotho and Vitamin D Axis In Endocrine-paracrine Renalmentioning
confidence: 99%
“…Fibroblast growth factor 23 (FGF23) is a protein with endocrine and paracrine effects . It is mainly synthesized by bone cells, but also other cells including immune cells and cardiomyocytes produce it .…”
Section: Introductionmentioning
confidence: 99%